2020
DOI: 10.1002/pssa.202000314
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Indium‐Tin‐Oxide Synaptic Transistor by Inkjet Printing Using Solution‐Processed ZrOx Gate Dielectric

Abstract: Inkjet-printed indium-tin-oxide (ITO) synaptic thin-film transistors (TFTs) using solution-processed high-k zirconium oxide (ZrO x) gate dielectric layer are reported. The effect of ZrO x annealing temperature from 300 to 500 C on the TFT performance is investigated. The optimized ZrO x gate dielectric layer of the ITO TFT can mimic biological synaptic response for the realization of intelligent computers and artificial bionic brain. The strong synaptic behavior of the ITO TFT exhibiting the on/off current rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Therefore, it is very different from the mechanism of forming an electric double layer (EDL) at the gate insulator and semiconductor interface. [27,31,34,56,[66][67][68][69][70][71] As shown in Figure 4a, in the initial state, before applying bias voltage to the gate and drain electrodes, positive metal ions and negative O ions are aligned in c-axis, and a lot of V o + exist. This is an equilibrium state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is very different from the mechanism of forming an electric double layer (EDL) at the gate insulator and semiconductor interface. [27,31,34,56,[66][67][68][69][70][71] As shown in Figure 4a, in the initial state, before applying bias voltage to the gate and drain electrodes, positive metal ions and negative O ions are aligned in c-axis, and a lot of V o + exist. This is an equilibrium state.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] Note that short-channel transistors can be available with oxide TFTs. [25,26] Table 1 shows the summary of the synaptic transistors based on MO semiconductors such as IGZO, [27][28][29][30] ITO, [31] IZO, [32] ZnO [33] and In 2 O 3 . [34] They use electrolytes or ferroelectric materials such as chitosan, [32] Ta 2 O 3 , [33] nanoparticles SiO 2 , [27] Gd 2 O 3 , [34] Al 2 O 3 [28] and HfZrO x [29] as gate insulator (GI) to…”
mentioning
confidence: 99%
“…Depending on the behavior of the defects (or residuals) clockwise (Bolat et al, 2019) or counterclockwise hysteresis (Bolat et al, 2020) can be observed in the transfer characteristics of the device. Counterclockwise hysteresis was reported with various dielectrics cured at low temperatures (T < 300 °C) such as AlO x (Liang et al, 2020a), GdO x (Zhou et al, 2020), and ZrO x (Kim et al, 2020). This behavior was usually complemented with unprecedentedly high mobility values compared to vacuum-based counterparts, which were reflected as mA range ON currents in the transistors (Daunis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that artificial synapses can be used in neuromorphic computing, memristive devices with a tunable memory window and high uniformity are vitally important. Among the candidates for artificial synapses, HfO 2 /TiO x memristors are preferred for their compatibility with CMOS and remarkable characteristics of resistance switching [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Compared with memristors based on the low-dimensional structure of TiO x from nanoparticles to nanorods [ 22 , 23 , 24 ], the advantage of HfO y /TiO x bilayers lies in two main aspects.…”
Section: Introductionmentioning
confidence: 99%